First report of Lutzomyia (Psychodopygus) bispinosa Fairchild and Hertig (Diptera. Psychodidae) from Costa Rica. - Herrero, Marco V. (1992)
Lutzomyia bispinosa had been reported from Belize (Williams 1970), Guatemala (Portes et al. 1987). Honduras (Fairchild and Hertig 1959), Nicaragua (Fairchild an Hertig 1959) and Panamá (Fairchild and Hertig 1951) which suggested its occurrence in Costa Rica. However, its presence in this country was suspected but not verified even after long term sampling of phlebotomine sandflies in different areas (Murillo and Zeledón 1985). During our epidemiological studies in Acosta San José prov.)we collected L. bispinosa. It has not been identified as vector of diseases in any area of America (D. Young, pers.com. 1991)